Macroeconomic and Fiscal Implications of Population Aging in Bulgaria - Onder, Harun; Pestieau, Pierre; Ley, Eduardo (World Bank, Washington, DC, 2014)
Bulgaria is in the midst of a serious demographic transition that will shrink its population at one of the highest rates in the world within the next few decades. This study analyzes the macroeconomic and fiscal implications of this demographic transition by using a long-term model, which integrates the demographic projections with social security, fiscal and real economy dimensions in a consistent manner. The simulations suggest that, even under fairly optimistic assumptions, Bulgaria's demographic transition will exert significant fiscal pressures and depress the economic growth in the medium and long term. However, the results also demonstrate that the Government of Bulgaria can play a significant role in mitigating some of these effects. Policies that induce higher labor force participation, promote productivity and technological improvement, and provide better education outcomes are found to counteract the negative consequences of the demographic shift.